Cyclooxygenase-2 is a target of microRNA-16 in human hepatoma cells - Agra Andrieu, Noelia (2012)
Cyclooxygenase-2 (COX-2) expression has been detected in human hepatoma cell lines and in human hepatocellular carcinoma (HCC); however, the contribution of COX-2 to the development of HCC remains controversial. COX-2 expression is higher in the non-tumoral tissue and inversely correlates with the differentiation grade of the tumor. COX-2 expression depends on the interplay between different cellular pathways involving both transcriptional and post-transcriptional regulation. The aim of this work was to assess whether COX-2 could be regulated by microRNAs in human hepatoma cell lines and in human HCC specimens since these molecules contribute to the regulation of genes implicated in cell growth and differentiation. Our results show that miR-16 silences COX-2 expression in hepatoma cells by two mechanisms: a) by binding directly to the microRNA response element (MRE) in the COX-2 3'-UTR promoting translational suppression of COX-2 mRNA; b) by decreasing the levels of the RNA-binding protein Human Antigen R (HuR). Furthermore, ectopic expression of miR-16 inhibits cell proliferation, promotes cell apoptosis and suppresses the ability of hepatoma cells to develop tumors in nude mice, partially through targeting COX-2. Moreover a reduced miR-16 expression tends to correlate to high levels of COX-2 protein in liver from patients affected by HCC. Our data show an important role for miR-16 as a post-transcriptional regulator of COX-2 in HCC and suggest the potential therapeutic application of miR-16 in those HCC with a high COX-2 expression.